An extended Tolerance Factor approach for organic–inorganic perovskites - Kieslich, Gregor (Royal Society of Chemistry, 2015)

(untitled) (Chem Sci)
Goldschmidt's concept of ionic Tolerance Factors was recently shown to be a valuable guideline for the preparation of new compounds within the field of organic–inorganic perovskites. Here, we extend this approach and calculate Tolerance Factors for over 2500 amine–metal–anion permutations of the periodic table. The results suggest the potential existence of more than 600 undiscovered hybrid perovskites including alkaline earth metal and lanthanide based materials.